FORMATION OF THE NATIONAL COMPETITIVE MODEL OF AGRICULTURAL ENTERPRISES DEVELOPMENT UNDER THE CONDITIONS OF GLOBALIZATION - Yuriy Kyrylov,; Viktoriia Hranovska,; Hanna Zhosan, (Scientific Journal of Pedagogy and Economics, 2021)
Institutional and innovative components of competitive development of agrarian enterprises have been found to be key and directly affect one another. Instruments for stimulating the innovative development of agricultural enterprises should be applied systematically, based on state innovation programs and strategies. In this context, the priorities of territorial innovative development of agro-formations are appropriate, provided the adaptation of existing and development of new state programs aimed at the development of innovative infrastructure, the formation of its new organizational forms, the support of innovative partnerships, the protection of intellectual property, and the promotion of venture financing. Also, the expected economic effects of the implementation of the model of institutional regulation of the competitive development of enterprises in the agrarian sector include the formation of important tools for improving the investment environment to ensure innovative production, maximize the effective use of the geopolitical position benefits, increasing export potential. The adaptive model of competitive development of the agrarian enterprises, the quintessence of which is based on econometric tools and the implementation of a set of economic and organizational tools and mechanisms for increasing competitiveness for leveling industry controversies and ensuring the formation of sustainable competitive advantages by agroformations through increased multiplier effect and synergy effect is developed.